2011
DOI: 10.1053/j.nainr.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygenation Monitoring: A Strategy to Detect Intraventricular Hemorrhage and Periventricular Leukomalacia

Abstract: Premature infants are at risk for intraventricular hemorrhage (IVH) and periventricular leukomalacia (PVL) theorized to be a result from fluctuations in cerebral blood flow. Monitoring cerebral oxygenation offers a method to observe changes in cerebral blood flow that may be beneficial for detecting and preventing IVH and PVL. This article explains the potential for cerebral oxygenation monitoring in detecting IVH and PVL using cerebral oximetry, reviews current knowledge known about cerebral oxygenation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…This re-emphasises the fact that these premature infants do feel pain, which we cannot ignore. For example, table 2 showed that there was moderate to severe pain in both the study and control groups, according to the Premature Infant Pain Profile (PIPP) scores (2). So, in addition to pacifiers and sucrose, we should use all possible measures to reduce pain and stress by carrying out an extremely gentle and brief examination.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…This re-emphasises the fact that these premature infants do feel pain, which we cannot ignore. For example, table 2 showed that there was moderate to severe pain in both the study and control groups, according to the Premature Infant Pain Profile (PIPP) scores (2). So, in addition to pacifiers and sucrose, we should use all possible measures to reduce pain and stress by carrying out an extremely gentle and brief examination.…”
Section: Dear Sirmentioning
confidence: 99%
“…The authors have shown significant differences in cerebral tissue oxygenation levels among four commercially available NIRS devices. Different measurement intervals, light wavelengths used, trends or absolute value measurements, light pathway distance (depends on probe size and manufacturer) and algorithm of venous to arterial blood ratio may lead to such a difference (2).We have a few queries in the manuscript.…”
Section: Cerebral Oxygenation Measurement In Preterm Neonates By Varimentioning
confidence: 99%
“…There are two main types of cerebral oximetry: absolute and trend monitoring. Absolute monitoring focuses on the meaning of the cerebral oxygenation value while the latter measures the change from a set baseline oxygenation value (8). Normal values for healthy individuals are described at 58-82% (5).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, cerebral oximetry has several disadvantages. First of all, oxygenation is measured only in regions underlying oximetry probes, so a large amount of the brain tissue remains unmonitored (8). Moreover, oxygenation values do not provide direct information on the amount of oxygen reaching the brain cells nor brain oxygen metabolism itself (12).…”
Section: Introductionmentioning
confidence: 99%
“…В последующие годы этот метод применялся для изучения патофизиологических из-менений в тканях при различных формах перина-тальной патологии [24,56,59], в сердечно-сосуди-стой хирургии с целью диагностики гипоксических состояний и профилактики послеоперационных осложнений [8,20,22,27]. Поскольку он осущест-вляется без использования радиоактивных материа-лов [13] и, в отличие от ультразвуковой допплероме-трии церебральных артерий, позволяет непрерывно оценивать изменение насыщения ткани мозга кис-лородом в процессе лечении патологических состо-яний, встал вопрос введения церебральной оксиме-трии в клиническую практику с диагностической и прогностической целью [19,26].…”
unclassified